Cancer amoenus Herbst, 1799, a junior subjective synonym of Atelecyclus undecimdentatus (Herbst, 1783) (Crustacea: Decapoda: Brachyura: Atelecyclidae) - Low, Martyn E. Y.; Ng, Peter K. L. (Zootaxa, 2012)
Schram & Ng (2012: 666) remarked that the name Cancer amoenus Herbst, 1799, “has been forgotten and the identity of the species unresolved for two centuries”, and commented briefly that this species is synonymous with Atelecyclus undecimdentatus (Herbst, 1783). We herein provide the necessary explanations for this synonymy.